Heparin-Binding Protein: A Diagnostic Biomarker of Urinary Tract Infection in Adults. (23rd April 2014) - Kjölvmark, Charlott; Påhlman, Lisa I.; Åkesson, Per; Linder, Adam
Abstract: Background. Urinary tract infections (UTIs) are associated with significant morbidity and high frequency of antibiotic prescription. Diagnosing UTI is often difficult, particularly in the critically ill patient and in patients with unspecific and mild symptoms. The standard rapid tests have limited value, and there is a need for more reliable diagnostic tools. Heparin-binding protein (HBP) is released from neutrophils and has previously been studied as a diagnostic and predictive biomarker in different bacterial infections. Methods. This prospective survey enrolled adult patients at 2 primary care units and 2 hospital emergency departments, to investigate in urine HBP as a biomarker of UTI. In addition, urine levels of interleukin-6, white blood cells, and nitrite were analyzed and compared with HBP. Based on symptoms of UTI and microbiological findings, patients were classified into different groups, UTI (cystitis and pyelonephritis) and no UTI. Results. Three hundred ninety patients were evaluated. The prevalence of UTI in the study group was 45.4%. The sensitivity and specificity for HBP in urine as a marker for UTI were 89.2% and 89.8%, respectively. The positive and negative predictive values were 90.2% and 88.8%, respectively. Heparin-binding protein was the best diagnostic marker for UTI, with an area-under-curve value of 0.94 (95% confidence interval, 0.93–0.96). Heparin-binding protein was significantly better in distinguishing cystitis from pyelonephritis, compared with the other markers. Conclusions. An elevated level of HBP in the urine is associated with UTI and may be a useful diagnostic marker in adult patients with a suspected UTI.